Prevalence and determinants of prehypertension (elevated blood pressure or high normal BP) according to different classifications in India during 2015–2021: Evidence from the large national surveys - Geetu Singh; Renu Agrawal; Sanjeev Kumar; Shubham Kumar; Rudresh Negi; Sonu Goel; Tanya Agarwal (PLoS ONE, 2025)
Background Since the advent of American Joint National Commission (JNC-7) guidelines, epidemiological studies have reported that prehypertension is a common presentation in the general population, with a prevalence of 25% to 55% globally. The present study aimed to estimate the prevalence of prehypertension (elevated blood pressure or high normal BP) and its determinants based on different standard classifications using the large population-based data from the fourth and fifth rounds of National Family Health Surveys (NHFS), India. We also intended to identify the trends of prehypertension between NFHS-4 and NFHS-5 at national, state and district levels. Methods We analyzed the data from the National Family Health Surveys (NFHS) 4 and 5 conducted in 2015−16 and 2019−20, respectively. Prevalence of pre-hypertension and its equivalent terms, elevated blood pressure and high normal BP was reported as per the Joint National Committee (JNC 7), 2017 American College of Cardiology/American Heart Association (ACC/AHA), and Indian Guidelines for Hypertension (IGH –IV) respectively. GeoDa (spatial and cluster maps) was used to compute Local Indicators of Spatial Association (LISA). We also calculated Moran’s Index to explain the data’s overall clustering and project the strength and patterns of spatial autocorrelation to represent district-level results. Results Prevalence of prehypertension (elevated blood pressure or high normal BP) showed an increasing trend across all three classifications from NFHS-4 to NFHS-5 in India (35.8% vs. 48.8% as per JNC 7, 6.1% vs 8.8% as per ACC/AHA and 12.5% vs 20.8% according to IGH-IV). Age > 29 years was significant risk factors for pre-hypertension in both the surveys as per JNC 7 and IGH -IV guidelines. Women had higher odds of having prehypertension according to all three guidelines in both surveys. Education had a protective effect across classifications as evident from NFHS-5 data, which was variable in the previous NFHS-4 survey. The prevalence of prehypertension (JNC 7/8) has increased above 50% in NFHS-5 survey in most states of India, namely, Delhi, most districts of Punjab, Himachal Pradesh, Haryana, Rajasthan, Uttarakhand, Uttar Pradesh, Chhattisgarh, Madhya Pradesh, Jharkhand, Odisha, Manipur, Mizoram, Arunachal Pradesh, Tamil Nadu, Lakshadweep and Andaman and Nicobar Islands. However, Goa, Sikkim, Assam, Nagaland and West Bengal demonstrated a declining trend in prevalence of prehypertension. In NFHS-5, 117 districts were observed as hotspots (“high-high” clustering) clustered zones, mostly in Arunachal Pradesh, Rajasthan, Madhya Pradesh, Uttar Pradesh, and Punjab. Conclusion We found a high prevalence of prehypertension in large population based survey in Indian population. The findings also highlighted marked differences in estimates of prehypertension (elevated blood pressure or high normal BP) based on different classifications. These results will help guide researchers, public health policymakers and clinicians to uniformly define prehypertension for its effective management. These trends should be considered as an interim warning signal to formulate guidelines with strong implementation of interventions to prevent and control prehypertension and hypertension.